INDONESIAN STUDENTS’ AND TEACHERS’ PERCEPTION OF GOOD EFL TEACHER’S CHARACTERISTICS - Putri, Eka Uliyanti; Yimmy, Yimmy; Antika, Ria (Lexeme : Journal of Linguistics and Applied Linguistics, 2022)
This research is aimed at knowing the results from the studentsâ€™ perception regarding the good characteristics teacher whether English teachers have fulfilled the good teacher characteristic and also knowing the teacherâ€™s view on the characteristics of being good EFL teacher. This research also aims at providing anyone concerned with ELF learning and teaching process, with a much better view so that there will be a more understanding toward the ideal figure that should be possessed by the teacher. This  research  is  conducted  in  into  a  few  subjects  ( 7 EFL  teacher  and approximately 80 students) in a certain time or period thus the result will just represent the point of view of the students and their teacher in that specific time. Since survey research requires large amount of data. The research was conducted in Global Institute and Polytechnic LP3I tangerang. The researchers use two questionnaire to gain the data. This research has purpose  that teachers could know their students perception and opinions about themselves. The result shows that teachers must have four aspects, they are technical knowledge, pedagogical skills, personal and interpersonal skills. So, the teachers can implement those aspects to encourage students to get involved in teaching learning process